Correction of vibration for classical free-fall gravimeters with correlation-analysis. (13th January 2017) - Wang, G; Hu, H; Wu, K; Wang, L J
Abstract: In a free-fall absolute gravimeter, a laser interferometer is used to track the falling retro-reflector. To buffer the reference retro-reflector from seismic noise, a low-frequency vertical vibration isolator is traditionally used. However, an isolation device is usually complicated and expensive. A strap-down system using a seismometer to record the vibration and correct the measurement resolves the issue, but the actual recorded vibration cannot be directly used because of signal transfer delay and amplitude attenuation. Nevertheless, by quadratically fitting the trajectory of the falling retro-reflector and the motion of the reference retro-reflector, we find that their residuals are significantly correlated. Moreover, the transfer delay and the amplitude attenuation can be calculated using correlation analysis. With this capability, a vibration correction method for absolute gravimeters is proposed and demonstrated. The transfer delay and the gain attenuation are determined from data of only 25 drops, and can be used to correct subsequent measurements. The method is also applied in the T-1 absolute gravimeter. The standard deviation of the measurement results is improved by a factor of 20 after correction in a noisy environment, and improved by a factor of 5 in a quiet environment. Compared with vibration isolators, the strap-down system using this correction method is much more compact, enabling its use in field conditions or even dynamic environments not suitable for vibration isolators.